Régimen rimpe y su incidencia en el cumplimiento de las obligaciones tributarias de los socios de la asociación Eloy Alfaro del Cantón Santo Domingo, año 2022. - Velasco Ortiz , Letty Abigail (2024)
Compliance with tax obligations has been of great importance, because through tax collection the State finances itself to provide public goods and services to its citizens. The main objective was to determine the impact of knowledge of the Simplified Regime for Entrepreneurs and Popular Businesses (RIMPE) on compliance with the tax obligations of the members of the Eloy Alfaro Association of the Santo Domingo canton, year 2022; To this end, the formal duties and tax obligations were identified, the level of compliance of the members of the Eloy Alfaro Association of the Santo Domingo canton was established and the incidence of knowledge of the RIMPE regulations on compliance with tax obligations was measured; Correlational research was used, in addition to field and documentary research; Inductive and deductive methods were applied to develop objectives. The research population was 92 members, 74 agreed to answer the survey that was used as an instrument for collecting information. As a result, it was found that the RIMPE has limited tax obligations and formal duties, it was determined that 81.08% of those surveyed are unaware of the reforms to the tax regulations and it was found that there is a significant relationship between knowledge of the RIMPE regulations and compliance with tax obligations. It was concluded that the more knowledge RIMPE taxpayers have, the better their level of compliance will be, which is why continuous training and advice was recommended.